Rekonstruksi Kewarisan Islam: Studi Hermeneutika Ibn Abbas atas Ayat-ayat Waris - Bachri, Syabbul (Institut Agama Islam Negeri Curup, 2020)
This study intends to analyze the hermeneutics of Ibn Abbas on the verses of inheritance in the Koran and their implications for the Islamic inheritance model. This research is a juridical normative study using content analysis and conceptual approaches. The results of research on Ibn Abbas's hermeneutics show that: first, daughters get a 2/3 portion if they are three or more in quantity. Second, in the case of gharawayn, the mother gets 1/3 of all inheritance not 1/3 of the remaining. Third, brothers or sisters can prevent the mother from getting 1/3 into 1/6 if they are 3 or more in quantity. Fourth, the grandfather has the same position as the father absolutely when the father died first. Fifth, the word